Silent architects of the jaw: A case series on odontome - Pareek, Avika; meena , DR. Manoj; baghla, Dr pallavi; Kaswan, Shobhit; singh, Dr kanishka; Agarwal, DR ARYAN; choudhary, DR. Tanishka (Indian Journal of Case Reports, 2026)
Odontomes are the most common benign odontogenic tumors of the jaw, which are usually slow-growing and non-aggressive. They are generally asymptomatic and diagnosed during routine radiographic investigations and are mostly associated with tooth eruption disturbances. Here, in this case series, we report six cases of compound and composite odontoma, with a relevant review of the literature. The present case series report covers cases of odontomes with an age group varying from 20 to 70 years, discussing clinical and radiographic features along with a brief review of the literature.